Кинематика переворота у жесткокрылых. II. Приемы переворота - Францевич, Л.И. (Вестник зоологии, 1982)
The general co-ordination plan of searching, rising, and clinging movements is modified in certain coleopteran taxa in accordance to peculiarities of the body build. One recognizes the symmetrical reverse over the head or around the pygidium, the rise on the antennae or on the elytrae, the stable tumbles and jumps. The stability conditions could be analyzed in the flat geometrical models. The turning modes are inherent for a certain taxon in extent corresponding to the uniformity of body proportions within this taxon. There is no strict correlation between the taxonomic status of an insect and the arsenal of righting modes it is armed with.